2019
DOI: 10.1016/j.ins.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion detection model of wireless sensor networks based on game theory and an autoregressive model

Abstract: A Wireless Sensor Network (WSN) security strategy is imperative to counteract security threats, and energy consumption directly affects the network life-time of a wireless sensor; thus an attempt to exploit a low-consumption Intrusion Detection System (IDS) to detect malicious attacks makes a lot of sense. Current Intrusion Detection Systems can detect just some specific attacks and the network life time is reduced due to their high energy consumption. For the purpose of energy limitation and high efficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…Additionally, Han et al [41], in their study to improve the network lifetime by reducing high energy consumption due to previous IDS mechanisms, also designed an intrusion detection model based on game theory and an improved autoregressive theory model. They showed that this new model takes the energy consumption of the intrusion detection process into consideration by being time-efficient, since in wireless sensor networks, the running time of the network processes is the main indicator of energy consumption of the system, also without consideration for sensor memory space.…”
Section: Wireless Sensor Network' Vulnerabilities and Threatsmentioning
confidence: 99%
“…Additionally, Han et al [41], in their study to improve the network lifetime by reducing high energy consumption due to previous IDS mechanisms, also designed an intrusion detection model based on game theory and an improved autoregressive theory model. They showed that this new model takes the energy consumption of the intrusion detection process into consideration by being time-efficient, since in wireless sensor networks, the running time of the network processes is the main indicator of energy consumption of the system, also without consideration for sensor memory space.…”
Section: Wireless Sensor Network' Vulnerabilities and Threatsmentioning
confidence: 99%
“…Intrusion detection mechanisms for traditional networks cannot be directly applied to WSNs because of the limited power, network bandwidth, computing capacity, and storage capacity in WSNs. The authors of [19] proposed an intrusion detection scheme for WSNs based on game theory and an autoregressive model. It is mentioned in [20] that a machine learning anomaly detection system for multicast communication could be constructed.…”
Section: Intrusion Detection Intrusion Detection Is Used To Detect Amentioning
confidence: 99%
“…Therefore, the sensor network security has attracted extensive attention, and it has also become an hot topic in the research field of computer science. Just as its name implies, network intrusion detection systems (IDS) is to detect the intrusion behaviors [1, 2]. By analyzing information collected from the key points of a computer network or a computer system, IDS can find out whether there are behaviors breaching a certain security strategy and signs of attack, and the purpose is to effectively protect the privacy and property safety.…”
Section: Introductionmentioning
confidence: 99%